Leyes, máximas y formas : Encuentros y desencuentros de la ciencia natural y el derecho en Francis Bacon - Manzo, Silvia (2020)
Within the framework of scholarly studies on the origins of the concept of the law of nature and departing from the links between this concept and the theological, legal and moral meanings of law, this paper examines the senses of law found in Bacon's jurisprudence and natural philosophy and the extent to which there are continuities and links between civil laws and laws of nature in his work. As for the laws of nature, it explores the concepts of summary law of nature and forms (laws of simple properties of bodies) and maxims of first philosophy. With respect to civil laws, it focuses on the natural law, the maxims of law and particular laws. It also deals with the maxims of first philosophy.